The Relationship Between Group and Organizational Factors on Misbehavior Performance in the Implementation of Patient Safety Incident Reporting - Terivenna Wijaya; Fathiyah Rahmah; Djazuly Chalidyanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
One issue in patient safety still a concern is the timeliness of reporting patient safety incidents. This study aims to analyze the relationship between the group, organizational, and mediator factors on misbehavior performance in implementing patient safety incident reporting in hospitals. The study was a descriptive study with a cross-sectional design conducted on all units in the hospital involving 174 respondents. Data was collected using a questionnaire that measured all variables on group factors, organizational factors, mediator factors, and misbehavior performance. Cross tabulation is used to analysis with a percentage difference of more than 20%. The results showed several groups and organizational factor namely cohesiveness, leadership, constructive type organizational culture, organizational climate, and control systems related to the ability to internalize organizational values and norms, belief in deviant behavior, and intentions to engage in deviant behavior. There is a correlation between mediator factors consisting of normative force, instrumental force, and intention to misbehave with deviant behavior in reporting patient safety incidents. Group and organizational factors are related to mediator factors, including internalization of organizational values and norms, beliefs of deviant behavior, and intentions. In addition, there is also a relationship between mediator factors and deviant behavior in reporting patient safety incidents.